3-Dimensional Accuracy of Dynamic Navigation Technology in Locating Calcified Canals - Jain, Sameer D.; Carrico, Caroline K.; Bermanis, Ido (Journal of endodontics, 2020)
This study aimed to present a novel dynamic navigation method to attain minimally invasive access cavity preparations and to evaluate its 3-dimensional (3D) accuracy in locating highly difficult simulated calcified canals among maxillary and mandibular teeth. Three identical sets of maxillary and mandibular 3D-printed jaw models composed of 84 teeth in their anatomic locations with simulated calcified canals (N = 138 canals) were set up on dental manikins. The Navident dynamic navigation system (ClaroNav, Toronto, Ontario, Canada) was used to plan and execute access preparations randomly with high-speed drills by a board-certified Endodontist. Two-dimensional (2D) and 3D horizontal, vertical, and angulation discrepancies between the planned and placed access preparations were digitally measured using superimposed cone-beam computed tomographic scans. Analysis of covariance models were used to evaluate the associations and the interaction between tooth type and jaw, the canal orifice depth, and the discrepancies between planned and prepared access cavities. The significance level was set at .05. The mean 2D horizontal deviation from the canal orifice was 0.9 mm, and it was significantly higher on maxillary compared with mandibular teeth (P < .05). The mean 3D deviation from the canal orifice was 1.3 mm, and it was marginally higher on maxillary teeth in comparison with mandibular teeth (P ≥ .05). The mean 3D angular deviation was 1.7 degrees, and it was significantly higher in molars compared with premolars (P < .05). The 3D and 2D discrepancies were independent of the canal orifice depths (P > .05). The average drilling time was 57.8 seconds with significant dependence on the canal orifice depth, tooth type, and jaw (P < .05). This study shows the potential of applying dynamic 3D navigation technology with high-speed drills to preserve tooth structure and accurately locate root canals in teeth with pulp canal obliteration.